The Role of Constitutions on Poverty: A Cross-National Investigation - Lanse Minkler; Nishith Prakash (Institute for the Study of Labor (IZA), 2015)
In this paper we use novel historical data on economics and social rights from the constitutions of 201 countries and an instrument variable strategy to answer two important questions. First, do economic and social rights provisions in constitutions reduce poverty? Second, does the strength of constitutional language of the economic and social rights matter? Constitutional provisions can be framed either more weakly as directive principles or more strongly as enforceable law. We find three important results. First, we do not find an association between constitutional rights generally framed and poverty. Second, we do not find an association between economic and social rights framed as directive principles and poverty. Third, we do find a strong negative association between economic and social rights framed as enforceable law and poverty. When we use legal origins as our IV, we find evidence that this result is causal. Our results survive a variety of robustness checks. The policy implication is that constitutional provisions framed as enforceable law provide effective meta-rules with incentives for policymakers to initiate, fund, monitor and enforce poverty reduction policies.
Keywords: I24; I32; I38; O1; O38; 330; economic and social rights; constitutions; enforceable law; directive principles; poverty; instrumental variables; legal origin